THE SIGNIFICANCE AND PROSPECTS OF ENGLISH AS AN INTERNATIONAL LANGUAGE - Juraeva Zarinakhon Bakhodir kizi (Bright Mind Publishing, 2025)
This article analyzes the role of English as an international language and the importance of enhancing its significance. Today, English is widely prevalent as a primary tool in global communication, economics, education, and culture. The article highlights the challenges and difficulties encountered in learning English and proposes effective solutions based on foreign experiences. Furthermore, it examines the development of English and its role in global cultural exchange, as well as the necessary approaches to improve English language learning within the education system. The aim is to identify methods focused on increasing the importance of English for learners and educational institutions.
Keywords: English Language, International Language, Global Communication, Education System, Culture, Economy, Foreign Experience